Perancangan Aplikasi Fit Your Weight Untuk Menghitung Berat Badan Ideal Berbasis Android - Setiadi, Ade; Handayani, Indri; Fadilah, Farah (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2021)
Knowledge about ideal body weight at this time is very much discussed, ideal body weight is certainly a good thing for health in themselves and appearance, For women and men weight is one thing that is often the main focus for health, those that are does not care about his weight so that he does not control his food patterns or irregular eating patterns, then see developments in this digital age all things are easily accessed through digital applications, with that basis we combine the android system with the calculation of ideal body weight, to find out body weight through the application certainly makes it easy and includes a fast way with it we made an android-based application to calculate whether the weight is ideal or not, so not only is a calculator, we also provide tips in it, with many methods of calculating body weight we chose to use the method Brocca and MIT App Inventor tools in making the application, because this method is simple enough to be used as a reference in the calculation, we hope that by making this application can facilitate the public in calculating the ideal body weight.